Pengembangan Media Mibogi (Mistery Box Materi Energi) pada Pembelajaran IPAS Kelas IV Sekolah Dasar - Prastyaningsih, Yuni; Pranata, Khavisa (University of Muhammadiyah Malang, 2024)
Utilizing limited and monotonous learning resources might trigger a loss of willingness to learn for students, and the inappropriate use of learning media can also affect the quality of learning. Moreover, in IPAS learning, especially energy material, concrete learning media is required to support learning. This research aims to develop cube-shaped media that will be developed into Mibogi (Mystery Box Energy Material) media. In addition, Mibogi media will also be tested to determine the feasibility and validity of Mibogi media as a learning media for IPAS. The ADDIE model development is applied in this research, and the stages are carried out sequentially. Two data collection techniques are: 1) employ a qualitative methodology using needs analysis, interview, and improvement input from experts, and 2) employ a quantitative approach using data processing of questionnaire answers into percentage values. The percentage value of this media is declared practical and very feasible based on the percentage value of 83% material experts and 96% media experts. When the outcomes of expert validation state that Mibogi media is considered practical and very feasible, the effectiveness test is given to educators, and the percentage value obtained is 85% with very feasible criteria. Then, implementing Mibogi to students on a limited scale test obtained 98% results, and a broad scale test obtained 93% results. Both show that Mibogi media is the perfect learning media for learning IPAS energy transformation material. Mibogimedia is as practical and feasible as IPAS learning in grade IV.